THE EFFECT OF HATHA YOGA ON DYSMENORRHOEA PAIN IN ADOLESCENT PRINCIPLE - Ummi Sa'adah; Kholisotin K; Zainal Munir; Handono FR; Abdul Hamid Wahid (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Dysmenorrhea is pain during menstruation caused by muscle contraction and imbalance of the hormone progesterone in the blood. One of the non-pharmacological treatments is Hatha yoga therapy, which is a type of relaxation technique that can reduce pain intensity by relaxing skeletal muscles. This study was purposed to determine the effect of Hatha Yoga Therapy on Dysmenorrhoea Pain in Adolescents at Darul Falah Islamic Boarding School. The design of this study was the